INFLUENCE OF THE CRANK MECHANISM POSITION IN THE MOTION OF AN OSCILLATING SIEVE (Journal of Engineering Studies and Research, 2021)
This article presents a study that aims to visualize the influence exerted by the position of the crank mechanism on the motion performed by the sieve supports respectively, on the displacement of an oscillating sieve. The study was oriented for a specific constructive case and involves the connecting rod position changing, the drive mechanism in relation to the horizontal, respectively at the angles 0 - 75° and -45 - 0°. Also, were identifying the variation of the angle described by the motion of the sieve support. From the obtained results analysis, it was found that in the case of 12.71° of the connecting rod angle, in relation to the horizontal, the lowest value of the angle described by the motion of the tie rod between the extreme points was obtained. Also, for the value of the connecting rod angle of approximately 6.5° equal angles described by the extreme positions of the sieve support in relation to the vertical were obtained. It is found that the variation of the connecting rod angle directly influences the variation of the angles described by the connecting rod in relation to the horizontal, the measured value being corresponding to the extreme points P1 and P2.
Keywords: oscillating motion, crank mechanism, connecting rod angle variation